2022
DOI: 10.3390/molecules27206973
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Analogues as Selective Estrogen Signaling Pathway Modulators: Structure–Activity Relationship

Abstract: Resveratrol is a plant-derived phytoalexin found in grapes, red wine and many other plants used in Asian folk medicine. It is extensively studied for pleiotropic biological activity. The most crucial are anticancer and chemopreventive properties. Resveratrol has also been reported to be an antioxidant and phytoestrogen. The phytoestrogenic activity of resveratrol was assayed in different in vitro and in vivo models. Although these works brought some, on the first look, conflicting results, it is commonly accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 59 publications
(112 reference statements)
0
7
0
Order By: Relevance
“…Pterostilbene, which exhibits estrogenic activity, mediated neuroprotective potential via mainly ER-α receptor, which activated the BCL-2 expression presumably through genomic estrogen signaling 42 . The distribution of hydroxyl groups in aromatic rings in the stilbenes makes them similar in chemical structure to endogenous and synthetic estrogens such as 17β-estradiol (E2) or diethylstilbestrol 43 . One early identified biological target of resveratrol was the estrogen receptor (ER), and the compound was classified as a phytoestrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Pterostilbene, which exhibits estrogenic activity, mediated neuroprotective potential via mainly ER-α receptor, which activated the BCL-2 expression presumably through genomic estrogen signaling 42 . The distribution of hydroxyl groups in aromatic rings in the stilbenes makes them similar in chemical structure to endogenous and synthetic estrogens such as 17β-estradiol (E2) or diethylstilbestrol 43 . One early identified biological target of resveratrol was the estrogen receptor (ER), and the compound was classified as a phytoestrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Despite various conflicting results, resveratrol is known as an estrogen mixed agonist/antagonist [ 35 , 36 ]. Recently, Kobylka et al have studied the ability of several methoxy- and hydroxy- resveratrol analogs to bind to the estrogen receptors [ 37 ]. Interestingly, the study revealed that DMU-212 does not exert binding affinity to ERα and Erβ [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kobylka et al have studied the ability of several methoxy- and hydroxy- resveratrol analogs to bind to the estrogen receptors [ 37 ]. Interestingly, the study revealed that DMU-212 does not exert binding affinity to ERα and Erβ [ 37 ]. The possible explanation of these results may be the lack of hydroxy groups in the structure of DMU-212 as -OH groups are suggested to possibly be responsible for binding estrogen receptors [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite some doubts, it has been already shown that the activation of SIRT1 by resveratrol protects the tibialis anterior muscle against age-associated sarcopenia via the preservation of normal autophagic flux [ 94 ]. Estradiol, as an endogenous activator of SIRT1, may hypothetically exhibit a very similar action, especially since resveratrol and estradiol share many molecular pathways [ 95 , 96 ].…”
Section: The Importance Of Estradiol–sirtuin-1 Signaling In the Physi...mentioning
confidence: 99%